Anaxagoras on the Light and Phases of the Moon - Couprie, Dirk (Hyperboreus, 2019)
This paper is a sequel of “Anaxagoras on the Milky Way and Lunar Eclipses” (Couprie 2017). Doxographic reports state that, according to Anaxagoras, the moon receives its light from the sun. Most authors understand it as meaning “the moon reﬂects the light of the sun”. This conﬂicts, however, with several testimonies that say clearly that the moon is a ﬁery stone, using essentially the same words as they do for the sun. O’Brien (1968) has already pointed out that the expression “the moon receives its light from the sun” is ambiguous. I argue that, within the general context of Anaxagoras’ astronomy, it is more probable that “the moon receives its light from the sun” means that the moon’s light is ignited by the sun.  Unfortunately, we do not possess information on Anaxagoras’ explanation of the moon’s phases. I suggest two options. In one, the moon is ignited by the sun when, during new moon, the two luminaries are close together. After that, the ﬁre spreads and extinguishes during the monthly cycle of phases. In the other, the moon’s phases are due to an invisible body, just like during a lunar eclipse.My conclusion from both papers is that Anaxagoras was not the great discoverer of the real cause of lunar eclipses and the moon light as he is depicted in recent publications. Anaxagoras inventively defended a coherent set of ideas that were already outdated: the ﬂat earth, the Milky Way caused by the earth’s shadow, the moon a ﬁery stone, and lunar eclipses caused by invisible heavenly bodies. As regards his general understanding of the heavenly phenomena, he is best described as a tragic ﬁgure.